Mechanical, Statistical, and Reliability Analysis of Sustainable Pervious Concrete Incorporating Calcium Carbide Waste and Broken Ceramic Tiles - M. Gora , Abdurra’uf; Fanen Johnn, Ker (Journal of Building Materials and Structures, 2025)
This study explores the development of sustainable pervious concrete by employing broken ceramic tiles (BCT) as a partial coarse aggregate replacement (7–20%) and calcium carbide waste (CCW) as a partial cement replacement (5–20%). The mechanical performance was assessed using tests for compressive and splitting tensile strength at 7 and 28 days. The correlation between these strengths was determined using statistical regression analysis. Additionally, a probabilistic reliability analysis was employed to assess the structural safety of the mixes in relation to a target strength of 15 MPa. The results show that while higher replacement levels considerably decrease strength because of increased porosity and reduced bonding, moderate replacement levels (5% CCW and 7% BCT) produce optimal mechanical performance. According to the results of the regression analysis, splitting tensile strength makes up around 5–6% of compressive strength at 28 days, and the relationship was statistically significant. Furthermore, the reliability analysis revealed that mixes with more than 15% combined replacement were unreliable, whereas the mix with 5% CCW and 7% BCT exhibits high structural reliability (β > 4.5). By confirming the complementary usage of CCW and BCT in pervious concrete, this study provides a risk-informed framework for producing sustainable mixtures that ensure both structural safety and environmental benefits.